Attachment Theory: How Marvelous Mother Guided An Adoption Child - Eka Mareta Suharyanti; Duwi Handayani; Adi Manggala Saputro; Abdillah Nugroho (Profesional Muda Cendekia Publishing, 2021)
The paper focuses on analyzing a mother who guides an adoption child reflected in The Blind Side movie. The researcher applies descriptive qualitative method in analysing the problem to find the data. The research questions are 1. What problems are faced by Leigh Anne's, as a mother? 2. What are the factors cause those problems? 3. How does Leigh Anne's solve the problems? The first data consisting of texts of the movie which is related to a mother guide adoption children and the second data that support the analysis. The technique of the data analysis is carried out by applying the close of mother and children using attachment theory by John Bowlby. The result shows that Leigh Anne Tuohy creates efforts in her supporting strategy such as adopted Oher to be her family, Mrs. Tuohy’s guide Oher to be an American football player. Part of that emotional funding for Leigh Anne is that finaly Oher can find his potential as a human being and find his identity to be a happy person like everyone else.The result is the power of love a marvelous mother can make Oher to be a successful American football player.